(untitled) (لســـانـنــا (LISANUNA): Jurnal Ilmu Bahasa Arab dan Pembelajarannya, 2026)
The advancement of digital technology has driven a transformation in the field of education, including Arabic language learning. One of the widely implemented innovations is the use of e-books as instructional media. This study aims to measure the effectiveness of e-book use in improving students’ speaking skills, particularly in the form of dialogue. A quantitative approach was employed using a quasi-experimental method with a one-group pretest-posttest design. The subjects consisted of elementary school students who were already familiar with using e-books in the learning process. Instruments included oral tests and speaking performance observation sheets. The results of the analysis showed a significant improvement in students’ speaking skills following the implementation of e-books. However, this effectiveness was also influenced by supporting factors such as teacher involvement, the quality of e-book content, and the intensity of speaking practice. These findings indicate that e-books can serve as effective media in Arabic language learning, provided they are supported by appropriate and interactive teaching strategies.